2019
DOI: 10.1007/s11165-019-9853-9
|View full text |Cite
|
Sign up to set email alerts
|

Perspective-Based Generic Questions as a Tool to Promote Student Biology Teacher Questioning

Abstract: In biological research, generic questions that are derived from perspectives (ways of looking at and thinking about life processes) help in generating specific questions. In this study, we used perspective-based generic questions as scaffolds to support student teachers in increasing the quality and quantity of their questions about biological topics. Fifteen student biology teachers were given an intervention to individually generate, in 15 min, as many questions as possible that they might ask in class about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Therefore, it is believed that it is revealed whether the students really grasp a concept or not with the help of such questions (Arslan, 2006). It is very important for teachers to ask higher level questions for students to acquire productive thinking skills (De Boer et al, 2021). The inclusion of high-level questions in lessons as part of the classroom discourse encourages students to think deeper and more reflectively (Eliasson et al, 2017).…”
Section: Related Literaturementioning
confidence: 99%
“…Therefore, it is believed that it is revealed whether the students really grasp a concept or not with the help of such questions (Arslan, 2006). It is very important for teachers to ask higher level questions for students to acquire productive thinking skills (De Boer et al, 2021). The inclusion of high-level questions in lessons as part of the classroom discourse encourages students to think deeper and more reflectively (Eliasson et al, 2017).…”
Section: Related Literaturementioning
confidence: 99%
“…Biology teachers experienced the change in their ability to ask better inquiry questions during a laboratory course in microbiology when the laboratory techniques were presented in an explicit and generalized manner, in the context of specific research questions [24]. Generic questions that are derived from perspectives (ways of looking at and thinking about life processes) help in generating specific questions [25]. When biology student teachers were asked to individually generate as many questions as possible that they may ask on a particular biological topic; first without using, and then using, a set of perspective-based generic questions.…”
Section: Introductionmentioning
confidence: 99%
“…When biology student teachers were asked to individually generate as many questions as possible that they may ask on a particular biological topic; first without using, and then using, a set of perspective-based generic questions. It was found that, using perspective-based generic questions, student teachers generated significantly more and higher quality questions [25]. In a study of Lin, Hong, Yang, and Lee [26], teaching practices of science teachers revealed that teachers asked more high-level questions requiring students to identify researchable questions, make hypotheses, design investigation procedures, or provide evidence-based conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…The education today, including the higher education which prepares the pre-service teachers, is required to apply active learning, in which the pre-service teachers are involved in efforts to construct their own knowledge. One way to fulfil this demand is by developing the questioning skills (Almeida, 2012;de Boer et al 2019).…”
Section: Introductionmentioning
confidence: 99%